A comparison of non-linear and linear approaches in developing goal scoring skills in elite youth football - Goyal, Rohan (2024)
Overall aim of this study was to investigate how to efficiently improve skilfulness in goal scor-ing in elite youth football. More specifically, an intervention was conducted to investigate whether non-linear pedagogy (NLP) or linear pedagogy (LP) is more efficient in improving goal scoring skill related actions. Suggested by prior research, more interventions should be conducted using representative test designs that are more closely aligned with the context of a football game environment (Bergmann et al., 2021; Roberts et al., 2020). The representativeness in this study was achieved by creating testing players under game-like physical loads, in a dynamic pressured situation with a defender, and creating an environment where adaptability was required. Concurrently, the study investigated what observable actions were connected in increasing skilfulness in goal scoring in terms of goal scoring percentage.